Pengukuran kualitas website dan digital payment e-commerce shopee menggunakan metode webqual 4.0 dan metode importance and performance analysis (IPA) - Kuncorosidi, Kuncorosidi; Agustian, Rio Dwi; Sopiawadi, Mutqi (Master Program in Accounting, Faculty of Economics, Universitas Islam Indonesia, 2024)
This study evaluates priority areas for quality improvement on the Shopee e-commerce platform involving users as the sample group. Quantitative methods utilizing the Webqual Index (WQI) and Importance Performance Analysis (IPA) were employed for analysis. Findings highlight attributes that require enhancement, such as interaction quality, file security, personal data confidentiality, product information alignment with original images, user-administrator communication facilities, and the need for expanded discussion space. In Shopee E-payment, improving service interaction quality and data privacy emerges as the primary focus. Enhancing platform usability involves offering diverse promotions for every e-payment transaction. Likewise, clarifying information quality, including easily understandable text and accurate transaction details, is crucial. This research provides crucial insights for enhancing Shopee's quality without disregarding user interests and the critical aspects of an e-commerce platform.